RULING ON HAVING TO SPEAK FALSEHOOD - Basha Al Bajali, Abul Firdaus Bayinat (International Journal For Research In Educational Studies, 2019)
Worship includes every human movement in life, and accordingly a person’s quest to take care of himself and his society is an obligatory matter, and he is rewarded for it as long as he adheres to what he must do in it. Because the meaning of compulsion is a comprehensive meaning that touches on many matters, and a person must be characterized by reconciliation with himself and with others. I have dealt with in this research some of the provisions of necessity in a number of the following issues: Pronouncing the word disbelief when necessary. Permissibility of lying and swearing against it when necessary Taqiyyah Permissibility Eating prohibited vaccinations Drinking wine because of thirst Then I interpreted the verses and explained the hadiths, criticism and deduction, and listed the opinions of the scholars and tried to explain the most correct one. Using the analytical method, then it showed the teachings to which the verses guide us, which must be applied in dealing with people through the applied approach.